Bibliometry of Costa Rica biodiversity studies published in the Revista de Biología Tropical/International Journal of Tropical Biology and Conservation (2000-2010): the content and importance of a leading tropical biology journal in its 60th Anniversary - Nielsen-Muñoz, Vanessa (2012)
Central America is recognized as a mega diverse “hot-spot” and one of its smaller countries, Costa Rica, as one of the world’s leaders in the study and conservation of tropical biodiversity. For this study, inspired by the 60th anniversary of the journal Revista de Biología Tropical, we tabulated all the scientific production on Costa Rican biodiversity published in Revista de Biología Tropical between 2000 and 2010. Most articles are zoological (62%) and 67% of authors had only one publication in the jounal within that period. A 54% of articles were published in English and 46% in Spanish. A 41% of articles were written in collaboration among Costa Rican institutions and 36% in collaboration with foreign institutions. The Collaboration Index was 2.53 signatures per article. Visibility in American sources was 56% in Google Scholar and 42.66% in the Web of Science, but the real visibility and impact are unknown because these sources exclude the majority of tropical journals. Revista de Biología Tropical is the main output channel for Costa Rican biology and despite its small size, Costa Rica occupies the 10th. place in productivity among Latin American countries, with productivity and impact levels that compare favorably with larger countries such as Brazil, Mexico, Argentina and Chile.